Ice Engineering: Elastic Property Studies on Compressive and Flexural Sea Ice Specimens. - Vaudrey,K. D. (1975)
A description of the elastic property studies on sea ice is presented along with a summary of the results of the experimental effort. Both laboratory and field tests were performed on compressive and flexural sea ice specimens to determine the following elastic material properties: compressive strength, flexural strength, and modulus of elasticity. Tests were conducted at four different ice temperatures, with the compression specimens also including two crystal orientations. The possible compressive failure modes and their causes are also discussed. (Author)